What Drives Employees' Innovative Behaviors in Emerging-Market Multinationals? An Integrated Approach - Jin, Shanyue; Li, Yannan; Xiao, Shufeng (Frontiers in Psychology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has severely damaged the global industrial supply chain and accelerated the digital transformation of the global economy. In such rapidly changing environments, multinational corporations (MNCs) should encourage employees to be more innovative in various fields than ever before. With the onset of the COVID-19 pandemic, employees have become psychologically anxious, their working conditions have deteriorated, and they are in danger of losing their jobs. In this study, we aim to address the question of whether servant leadership facilitates the innovative behavior of employees working in emerging-market MNCs when servant leadership is adopted within the firms. In addition, we explore the mediating roles of work–life balance and psychological stability perceived by employees, and the moderating role of organizational climate in the relationship between servant leadership and MNC employees’ innovative behavior. In doing so, we collected data from a sample of 307 Chinese employees who are employed by five different Chinese MNCs from the Internet, information technology, electronics, and e-commerce industries. Based on a sample of survey data collected from employees of Chinese MNCs, we empirically test these ideas by specifically examining how servant leadership may shape the innovation behavior of employees in these MNCs. The results suggest that servant leadership positively influences employees' innovative behavior, and that the contribution of servant leadership to employees’ innovative behavior is mediated by work–life balance and psychological stability as well as moderated by the degree of organizational climate. Moreover, the different organizational climates of these MNC employees are also expected to significantly shape the relationship between servant leadership and employees’ innovative behavior. This study enriches our understanding of the importance of servant leadership in driving the innovative behaviors of employees in emerging-market MNCs and provides new insights into the mechanisms through which emerging-market MNCs can motivate their employees to be more innovative in their jobs. Thus, this study contributes to the research on human resource management by offering important implications vis-à-vis how MNCs manage their employees more effectively in addressing and responding to the dramatically changing global landscape in the post COVID-19 era.